2013
DOI: 10.1016/j.ejca.2012.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Predictive role of plasma vascular endothelial growth factor for the effect of celecoxib in advanced non-small cell lung cancer treated with chemotherapy

Abstract: Aim of the study: The primary purpose of this study is to investigate if pretreatment plasma levels of vascular endothelial growth factor (VEGF) are predictive of the effect of celecoxib on survival in advanced non-small cell lung cancer (NSCLC) treated with palliative chemotherapy. A secondary objective is to describe the course of plasma VEGF levels during and after treatment with cytotoxic chemotherapy combined with celecoxib or placebo. Methods: In a previously published double-blind multicenter phase III … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…When the index of expression of COX-2 was more than 4, the patients with celecoxib had better OS and PFS than those without celecoxib [ 14 ]. If pretreatment plasma levels of vascular endothelial growth factor (VEGF) were restricted to lower than 200 pg/ml, celecoxib had a protective effect on survival compared with placebo [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the index of expression of COX-2 was more than 4, the patients with celecoxib had better OS and PFS than those without celecoxib [ 14 ]. If pretreatment plasma levels of vascular endothelial growth factor (VEGF) were restricted to lower than 200 pg/ml, celecoxib had a protective effect on survival compared with placebo [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical findings indicate that vascular endothelial growth factor (VEGF) may rescue cancer cells from celecoxibinduced apoptosis, and that anti-metastatic effects of COX-2 inhibitors may improve during simultaneous VEGF blockade [20]. In a previous subset analysis of 107 patients from the original randomized trial, we found that low pretreatment plasma levels of VEGF were predictive of a positive effect of celecoxib on survival [21]. Interestingly, a similar finding was obtained in a smaller phase II study for breast cancer patients treated with cyclophosphamide and celecoxib [22].…”
Section: Discussionmentioning
confidence: 84%
“…Thus, selective COX-2 inhibitors may have beneficial effects on not only quality of life but survival in infants with NB. Clinical studies also reported that the selective COX-2 inhibitor celecoxib prevented the occurrence of colorectal adenomas [33] and showed some therapeutic effects in patients with breast [34] , head and neck [35] , cervical [36] , non-small cell lung [37] , colorectal [38] and ovarian cancer [39] . Of note, a recent clinical study described that oral celecoxib prevented the progression of neuroblastoma [40] .…”
Section: Discussionmentioning
confidence: 99%